Efficacy of Solvent Extracts of Nelumbo nucifera Gaertn (Nelumbonaceae) and Melia dubia Cav (Meliacae) against Fall Armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) - Suguna, G.; Arivudainambi, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Spodoptera frugiperda is a significant pest of economic importance due to its high rate of reproduction, potential for damage and capacity to consume several types of plants. It has become resistant to numerous chemical pesticides. It is challenging to control this pest in field due to the lack of host plant resistance and inadequate management techniques. Bioactive molecules of plant origin hold potential alternative for the chemical pesticides. In the present study, leaves of Nelumbo nucifera and Melia dubia were extracted with acetone, ethyl acetate and benzene. All the solvent extracts of N. nucifera and M. dubia exhibited larval, pupal and adult malformation of S. frugiperda. At higher doses, these plant extract exerted medium antifeedancy. In regarding, insect growth regulatory (IGR) activity, maximum of 33.33% larval malformation at 7% benzene extract of M. dubia, 53.33% pupal malformation at 7% benzene extract of N. nucifera and 33.33% adult malformation at 5% ethyl acetate extract of N. nucifera was recorded. In comparing all the extracts, the benzene extract of N. nucifera showed maximum IGR activity against S. frugiperda at 5%.